The Rhetoric of Early American Ethnography: Framing Politics in the Texts by Crèvecoeur, Jefferson and Tyler (SCHOLARS: Journal of Arts & Humanities, 2022)
This paper studies early American manners and customs chapters in the texts written by J. Hector St. John De Crèvecoeur, Thomas Jefferson, and Royall Tyler as precursors to ethnography, and demonstrates how these writers use ethnographic mode to explore their contemporary political issues. The paper argues that the ethnographic accounts in these chapters are less the objective representations of cultures than the political views shrouded in ethnographic modes. The argument then is that the chapters should be treated as rhetorical frames. To exemplify this argument, the paper analyzes Crèvecoeur’s Nantucket sequence in Letters from an American Farmer and demonstrates its pro-capitalist political aspirations. The paper also takes up Jefferson’s descriptions of Native Americans in Notes on the States of Virginia and shows how he used the ethnographic descriptions and scientific methodology to test whether the European settlers could prosper in the new land—particularly in the early nineteenth-century context of the theory of biological degeneration that assumed that a particular geographic context could determine the intellectual and moral aspects of a race. Finally, the paper reads the ethnographic accounts in Tyler’s The Algerine Captive and demonstrates how the whole book was a persuasive attempt to solidify support for the strong national government amidst the continued opposition within American states to join the new federal structure instituted by the new 1789 Constitution.